Screening of Copper-Resisting Hydrocarbon Degrading Bacteria and Biosurfactant Production - Nur Nadiah, Zainal Ariff (2016)
Four bacterial isolates that were known to degrade hydrocarbons were screened for copper (Cu) resistance and biosurfactant production. Based on spectrophotometry, isolate D had the highest growth (p<0.05) followed by isolate A, isolate C and isolate B with the least growth. Biosurfactant screening assays confirmed that both isolates D and A produced biosurfactant. The dry-weight of biosurfactant obtained from partial purification suggested that there was a direct relationship between the number of cells present and the amount of biosurfactant produced. Gram staining showed that isolate D and isolate A are gram negative and gram positive respectively. The results showed that gram negative bacteria was able to show tolerance towards 20.0 mg/L Cu, possible by secretion of biosurfactant to chelate Cu ions in reducing the metal toxicity.